2010
DOI: 10.1038/nsmb.1927
|View full text |Cite
|
Sign up to set email alerts
|

Rad51 protects nascent DNA from Mre11-dependent degradation and promotes continuous DNA synthesis

Abstract: The role of Rad51 in an unperturbed cell cycle has been difficult to dissect from its DNA repair function. Here, using electron microscopy (EM) to visualize replication intermediates (RIs) assembled in Xenopus laevis egg extract we show that Rad51 is required to prevent the accumulation of ssDNA gaps at replication forks and behind them. ssDNA gaps at forks arise from extended uncoupling of leading and lagging strand DNA synthesis. Instead, ssDNA gaps behind forks, which are exacerbated on damaged templates, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
564
8
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 494 publications
(615 citation statements)
references
References 46 publications
40
564
8
3
Order By: Relevance
“…[3][4][5] This notion is strengthened by our observation that WRNIP1 functions in the same pathway as BRCA2, as proved by their physical interaction and lack of additive effect on DNA nascent strand degradation when we downregulated both in cells. The inability to form a RAD51-coated nucleofilament renders BRCA2-deficient cells susceptible to MRE11 nucleolytic degradation.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…[3][4][5] This notion is strengthened by our observation that WRNIP1 functions in the same pathway as BRCA2, as proved by their physical interaction and lack of additive effect on DNA nascent strand degradation when we downregulated both in cells. The inability to form a RAD51-coated nucleofilament renders BRCA2-deficient cells susceptible to MRE11 nucleolytic degradation.…”
supporting
confidence: 57%
“…In this regard, breast cancer type 2 susceptibility protein (BRCA2) and radiation sensitive 51 protein (RAD51) protect nascent DNA strands from the pathologic degradation mediated by the exonucleolytic activity of meiotic recombination enzyme 11 (MRE11), implicating a distinct role from the repair of lesions formed at stalled replication forks. [3][4][5] Despite extensive research, how these HR components accomplish the resolution of fork stalling, and whether other proteins collaborate with them in this task, has not yet been fully elucidated.…”
mentioning
confidence: 99%
“…Regardless of their source, postreplicative ssDNA gaps can certainly contribute to explain the observed accumulation of RAD51 in PARG-depleted cells. Intriguingly, RAD51 was previously reported to limit ssDNA accumulation at yeast and Xenopus replication forks, especially in response to genotoxic stress (40). Furthermore, RAD51 itself and several HR and Fanconi anemia factors were shown to prevent excessive degradation of newly synthesized DNA in response to replication stress (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in Xenopus cell extracts showed that formation of RAD51 filaments at stalled replication protects from degradation by the Mre11 nuclease (Hashimoto et al 2010). Similar observations were made in BRCA2-deficient mammalian cells, in which fork protection was found to be independent of RAD54, suggesting that it is the RAD51 -ssDNA filament structure and not its ability for DNA strand invasion that protects from Mre11 degradation (Schlacher et al 2011).…”
Section: Reversibility At the Rad51 Nucleoprotein Filament Stage: Resmentioning
confidence: 99%